Meritokrasi sebagai Nilai Islam: Studi Perbandingan Sistem Manajemen Aparatur Sipil dalam Hukum Indonesia dan Hukum Islam - Prasetyo, Eko; Zaenal Arifin, Muchamad (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Meritocracy serves as a normative foundation in the management of Indonesia’s State Civil Apparatus (ASN); however, its implementation is often hindered by political patronage, regulatory fragmentation, and weak institutional integrity. Although recruitment and promotion mechanisms based on merit have been formalized, various challenges continue to obstruct the realization of fairness and bureaucratic professionalism. In contrast, Islamic political thought offers the concept of ahl al-kifāyah, which emphasizes the integration of competence (al-quwwah) and moral integrity (al-amānah) in public leadership, as reflected in the Qur’an and fiqh siyasah literature. This study aims to analyze the construction of meritocracy in ASN management in Indonesia and compare it with the principles of ahl al-kifāyah. Using a normative-comparative legal research approach and literature review, the study examines legislation, policy documents, and classical and contemporary Islamic sources.The findings indicate that, conceptually, Indonesia’s merit system aligns with Islamic principles, particularly regarding competence and accountability. However, ethical and transcendental values have not been fully institutionalized as part of leadership legitimacy. Based on these findings, this study proposes an Islamic Meritocracy Framework that integrates technical competence, moral integrity, and value-based leadership into ASN recruitment and management. This framework provides a normative perspective to strengthen governance, uphold ethical standards, and support civil service reform in Indonesia